2018
DOI: 10.3389/fendo.2018.00504
|View full text |Cite
|
Sign up to set email alerts
|

Variant Alleles of the ESR1, PPARG, HMGA2, and MTHFR Genes Are Associated With Polycystic Ovary Syndrome Risk in a Chinese Population: A Case-Control Study

Abstract: Polycystic ovary syndrome (PCOS) is the most common endocrinopathy in women of reproductive age, with a prevalence of 6–8%. Although the etiology of PCOS has been investigated extensively, the association between genetic predisposition and PCOS risk is largely unknown. In this study, we genotyped 63 SNPs in 10 genes among 361 PCOS patients and 331 healthy controls in a Chinese Han population. The following variant alleles were significantly associated with decreased PCOS risk: ESR1 rs9340799 (P = 0.000), PPARG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 39 publications
0
23
0
1
Order By: Relevance
“…Research confirmed that PPARG rs709154 and ESR1 rs1999805 are significantly associated with PCOS risk in a Chinese population [37]. MMP9 may also be involved in the pathogenesis of PCOS [38].…”
Section: Ppi Network Analysismentioning
confidence: 84%
“…Research confirmed that PPARG rs709154 and ESR1 rs1999805 are significantly associated with PCOS risk in a Chinese population [37]. MMP9 may also be involved in the pathogenesis of PCOS [38].…”
Section: Ppi Network Analysismentioning
confidence: 84%
“…In a study by Zhao L et al, ESR1 polymorphisms were reported to be associated with hypertension and diabetes 28 . A case–control study by Jiao X et al, documented that altered expression of ESR1 can influence the risk of PCOS and its upregulation may contribute to abnormal follicular development 29 , 30 . Prostaglandin-endoperoxide synthase ( PTGS2) is a key enzyme for biosynthesis of the inflammatory hormone prostaglandin.…”
Section: Resultsmentioning
confidence: 99%
“…Electronic database search yielded 161 studies, after applying strict inclusion and exclusion criteria total 23 articles were found suitable for the inclusion in the present meta-analysis.. Figure 1 shows the different phases of the study selection. Information was collected from 22 articles that associated MTHFR gene C677T polymorphism and PCOS (Glueck et al, 1999; Sills et al, 2001; Tsanadis et al, 2002; Lee et al, 2003; Orio et al, 2003; Palep-Singh et al, 2007; Choi et al, 2009; Bayram et al, 2010; Karadeniz et al, 2010; Idali et al, 2012; Jain et al 2012; Kazeerooni et al, 2013; Jiang et al, 2015; Naghavi et al, 2015; Qi et al, 2015; Carlus et al, 2016; Geng et al, 2016; Ozegowska et al, 2016; Sazafarowska et al, 2016 ; Wu et al, 2016; Jiao et al, 2018; Amuhtar and Amohaidi, 2019) (Table 1). In two studies, authors (Palep-Singh et al, 2007; Carlus et al, 2016) included two group of samples..…”
Section: Resultsmentioning
confidence: 99%
“…First of all, Glueck and colleagues (1999) have reported an association between MTHFR C677T polymorphism and PCOS. Since then, several reports are published regarding MTHFR C677T polymorphism as a risk factor for PCOS with positive (Wu et al, 2016; Jiao et al, 2018; Amuhtar and Amohaidi, 2019)as we as negative (Sills et al, 2001; Lee et al, 2003; Orio et al, 2003) results. Hence, the aim of the present study was to explore whether the MTHFR C677T polymorphism is associated with susceptibility to polycystic ovary syndrome (PCOS).…”
Section: Introductionmentioning
confidence: 99%